Prediction Rules for Ruling Out Endocarditis in Patients With Staphylococcus aureus Bacteremia. (16th July 2021) - van der Vaart, Thomas W; Prins, Jan M; Soetekouw, Robin; van Twillert, Gitte; Veenstra, Jan; Herpers, Bjorn L; Rozemeijer, Wouter; Jansen, Rogier R; Bonten, Marc J M; van der Meer, Jan T M
Abstract : In patients with Staphylococcus aureus bacteremia, VIRSTA can be used to rule out endocarditis, but at the expense of a high number of patients classified as high risk and thus requiring TEE. The POSITIVE and PREDICT scores require adjustment. Abstract: Background: Staphylococcus aureus bacteremia (SAB) is in 10% to 20% of cases complicated by infective endocarditis. Clinical prediction scores may select patients with SAB at highest risk for endocarditis, improving the diagnostic process of endocarditis. We compared the accuracy of the Prediction Of Staphylococcus aureus Infective endocarditiseTime to positivity, Iv drug use, Vascular phenomena, preExisting heart condition (POSITIVE), Predicting Risk of Endocarditis Using a Clinical Tool (PREDICT), and VIRSTA scores for classifying the likelihood of endocarditis in patients with SAB. Methods: Between August 2017 and September 2019, we enrolled consecutive adult patients with SAB in a prospective cohort study in 7 hospitals in the Netherlands. Using the modified Duke Criteria for definite endocarditis as reference standard, sensitivity, specificity, negative predictive (NPV), and positive predictive values were determined for the POSITIVE, PREDICT, and VIRSTA scores. An NPV of at least 98% was considered safe for excluding endocarditis. Results: Of 477 SAB patients enrolled, 33% had community-acquired SAB, 8% had a prosthetic valve, and 11% a cardiac implantable electronic device. Echocardiography was performed in 87% of patients, and 42% received transesophageal echocardiography (TEE). Eighty-seven (18.2%) had definite endocarditis. Sensitivity was 77.6% (65.8%–86.9%), 85.1% (75.8%–91.8%), and 98.9% (95.7%–100%) for the POSITIVE (n = 362), PREDICT, and VIRSTA scores, respectively. NPVs were 92.5% (87.9%–95.8%), 94.5% (90.7%–97.0%), and 99.3% (94.9%–100%). For the POSITIVE, PREDICT, and VIRSTA scores, 44.5%, 50.7%, and 70.9% of patients with SAB, respectively, were classified as at high risk for endocarditis. Conclusions: Only the VIRSTA score had an NPV of at least 98%, but at the expense of a high number of patients classified as high risk and thus requiring TEE. Clinical Trials Registration: Netherlands Trial Register code 6669.